Gaya Komunikasi Habib Ja’far dalam Tayangan Youtube Login Ja’far Onad Episode 15 Perang Takjil - Maulana Azmi; Ade Budi Santoso (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This study discusses the communication style presented by Habib Ja'far on the YouTube show Login Ja'far Onad Episode 15 Perang Takjil. This study uses the Aristotelian Rhetoric approach to determine how Habib Ja'far's communication style is on the YouTube show Login Ja'far Onad Episode 15 Perang Takjil. The results of this study indicate that in Habib Ja'far's communication style there is a Pathos aspect, namely the way Habib Ja'far conveys his emotions to the person he is talking to and the way he builds an emotion in communicating, then Habib Ja'far's communication style has an Ethos aspect, namely Habib Ja'far's character in communicating and finally there is a Logos aspect, namely how Habib Ja'far uses and chooses sentences in communicating so that they can be understood by the listener and the person he is talking to.